Efficacy of emerging therapies versus traditional therapies in the treatment of hypertrophic scars and keloids: a systematic review - Alzate, Juan; Villamil-Guevara, Johanna; Adarme-Malaver, Juliana; Gutiérrez-Ochoa , Laura; Acevedo Piedrahita , Laura; Pinilla-Obregon , Mariana (Aesthetic Medicine, 2025)
Introduction: Hypertrophic scars and keloids are abnormal wound-healing alterations that disproportionately affect populations of African, Asian, and Latin descent. Traditional therapies, such as surgery, corticosteroids, and laser treatments, demonstrate limited effectiveness and frequent recurrence. Emerging therapies, including mesenchymal stem cells and growth factors, hold promise for improved inflammatory regulation and tissue remodeling.Objective: To compare the efficacy and safety of emerging therapies versus traditional treatments in reducing hypertrophic scars and keloids, evaluating aesthetic outcomes, scar size, and recurrence rates.Methods: A systematic review was conducted in accordance with PRISMA guidelines, including 8 studies with 525 participants. The interventions assessed comprised mesenchymal stem cells, platelet-rich plasma, and triamcinolone-laser combinations. Primary outcomes were volume reduction, aesthetic improvement, and decreased recurrence.Results: Emerging therapies, such as platelet-rich plasma, showed significant reductions in the Vancouver Scar Scale (p